Decolonising biblical hermeneutics in the (South) African context - H. Ramantswana (Acta Theologica)
The recognition of social location as a heuristic device in biblical hermeneutics does not necessarily equate to the production of radical and alternative knowledge. From our own social location (Africa), biblical hermeneutics has to deal with the dynamics of coloniality. Africa, especially South Africa as a social location, is still burdened by coloniality. The orientation of African biblical hermeneutics has to be decolonial if it is to overcome the persistence of coloniality by privileging African knowledge systems and African thinkers. It also has to unmask the structures of coloniality that continue to destabilise the African imagination. The emergence of African biblical hermeneutics does not imply that the colonial systems have been overcome – coloniality is able to survive and thrive even under the tag “African”.